A semantic driven approach for requirements consistency verification. (2015) - Gargiulo, Francesco; Gigante, Gabiella; Ficco, Massimo
Consistency and completeness are the main quality attributes to be guaranteed in software development. Software engineering community has largely studied consistency, together with completeness, in the last decade, to improve quality of software products and to reduce costs. Different approaches have been defined to detect and manage inconsistencies in software life cycle. The adoption of ontologies seems promising to achieve the proper level of formalism and to argue on quality properties. This paper presents a survey of the main approaches to consistency in different tasks of software engineering, focusing on the requirement engineering tasks, and proposes an ontological engineering approach to detect inconsistencies among a set of requirements written in natural language.